ANALISIS TEORI PENDEKATAN SITUASIONAL UNTUK GURU WALI KELAS BAGI TRANSFORMASI KEBERHASILAN PEMBELAJARAN SISWA [ANALYSIS OF THE SITUATIONAL APPROACH THEORY FOR HOMEROOM TEACHERS FOR TRANSFORMING ACHIEVEMENT OF STUDENT LEARNING] - Tikno Iensufiie (Polyglot, 2020)
Homeroom teachers have many other tasks besides teaching such as guiding their students in an organized manner as a group towards the same goal of a successful learning process. The homeroom teacher has a mandate from God to have a positive influence as "Salt and Light" which enlightens students to become better people. The purpose of this paper is to analyze the function of the Situational Approach Theory with indicators of student competence and commitment. This activity can be run through classroom observations as can be practiced by the homeroom teacher in order to provide a better learning process.BAHASA INDONESIA ABSTRAK: Guru wali kelas memiliki tugas selain mengajar, yaitu memimpin murid-muridnya secara terorganisasi, sebagai kelompok menuju tujuan yang sama, yaitu kesuksesan proses belajar & mengajar. Guru wali kelas memiliki amanat agung dari Tuhan dalam memberikan pengaruh positif sebagai "Garam dan Terang" dan memberikan pencerahan pada muridnya untuk bertransformasi menjadi pribadi yang lebih baik. Tujuan tulisan ini adalah untuk menganalisis penggunaan Teori Pendekatan Situasional menggunakan indikator kompetensi dan komitmen siswa. Kegiatan ini dapat dipraktekkan oleh guru wali kelas melalui pengamatan kelas, dengan tujuan agar dapat memberikan proses pembelajaran yang lebih baik.